Upaya Meningkatkan Kemampuan Siswa dalam Menginterprestasikan Peta Tentang Pola dan Bentuk Muka Bumi Melalui Media Peta - Endang Sriningsih (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2015)
Education is an investment in human resources. To get quality human resources, it is necessary to pay attention to several interrelated factors, including infrastructure, education, curriculum, education personnel and community participation. Therefore, teachers have a very important role in the world of education. Educational media in the form of maps were chosen in this study considering the media map is a media that does not require a large place and easy to use. How the application of map media in improving student learning outcomes in interpreting maps about the pattern and shape of the earth. This class action research was conducted in two cycles, consisting of four stages, namely action planning, observation and reflection. In the first cycle of learning, student test results increased by 33.11% ie from the results of pre-cycle tests 61.08 to 73.65 The average value obtained by students on the first cycle test first meeting and the results of the first cycle at the second meeting increased to 74.70. In the second cycle both at the first meeting and the second meeting increased by 89.47%. while the minimum completeness limit of 70 and the average students get at the first meeting is 80.54 to 85.54.